Kirkgecit Formation (Middle Eocene-Oligocene): An example of tidal flat and stormy shelf complex (NNW of Elazig) - Turkmen, I.; Inceoz, M. (My University, 1999)
Kirkgecit Formation which covers large areas in Eastern Anatolia, crops out approximately in a NE-SW direction in the Elazig Basin. In the study area, Keban Metamorphics (Permo-Triassic), Elazig Magmatics (Cenonian) and Harami Formation (Upper Maastrichtian) form the base of this basin. On the basis of the facies analyses of the measured stratigraphic section, seven facies and three facies assamblages were identified. These facies are; graded calcarenite, hummocky cross-bedded calcarenite, planar horizontal laminated sandstone, small scale planar cross-laminated sandstone, trough cross-bedded sandstone, gray mudstone, and benthic foraminiferous packstone. The tidal flat facies consists of horizontal laminated sandstones with intense biogenic structures; small scale planar cross bedded sandstones and sandstones with herringbone-cross bedding. The inner shelf facies is found in the intermediate levels of the formation and represented by the gray mudstones and calcarenite with hummocky cross-bedded characterizing the stormy periods in its lower levels and by packstones with benthic foraminifera at its upper levels. The outer shelf facies becomes coarser upward and consists of alternating sequences. This sequences is made up of gray mudstones and packstone with bentic foraminifera at its lower levels and Bouma type graded bedded calcarenite at its upper parts.
Kirkgecit Formasyonu (Orta Eosen-Oligosen): Gel-git duzlugu ve firtinali self kompleksine bir ornek (Elazig KKB'si)
Keywords: Elazig; Kirkgecit Formation; Shelf; Tidal flat